In the Beginning Was the Deed. (8th April 2013) - Cockburn, David
Abstract Winch's readings of Wittgenstein and Weil call for a significant rethinking of the relation between "metaphysics" and "ethics." But there are confusions, perhaps to be found in all three of these writers, that we may slip into here. These are linked with the tendency to see idealist tendencies in Wittgenstein, and with his remark that giving grounds comes to an end, not in a kind of seeing on our part, but in our acting. The sense that we think we see in this suggestion is dependent on a distorted conception of "justification." Getting clear about this involves coming to appreciate just how much of our nature as ethical beings is engaged when we do philosophy.